2021
DOI: 10.3390/genes12030365
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmologic Manifestations of Primary Sjögren’s Syndrome

Abstract: Sjögren’s syndrome (SS) is a chronic, progressive, inflammatory, autoimmune disease, characterized by the lymphocyte infiltration of exocrine glands, especially the lacrimal and salivary, with their consequent destruction. The onset of primary SS (pSS) may remain misunderstood for several years. It usually presents with different types of severity, e.g., dry eye and dry mouth symptoms, due to early involvement of the lacrimal and salivary glands, which may be associated with parotid enlargement and dry eye; ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 154 publications
0
22
0
Order By: Relevance
“…In the present study, a newly-developed eye mask producing heating in the first phase of session and heating plus vibration in the second phase has been used for the treatment of patients with symptomatic MGD. Since MGD may be associated with other systemic diseases such as rosacea and Sjogren syndrome [ 21 , 22 ], a heterogeneous MGD population was enrolled to obtain results that are generalizable to the real-life clinical practice. This preliminary analysis showed that half hour after the first mask session, tear film parameters (NIBUT and LLT) improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a newly-developed eye mask producing heating in the first phase of session and heating plus vibration in the second phase has been used for the treatment of patients with symptomatic MGD. Since MGD may be associated with other systemic diseases such as rosacea and Sjogren syndrome [ 21 , 22 ], a heterogeneous MGD population was enrolled to obtain results that are generalizable to the real-life clinical practice. This preliminary analysis showed that half hour after the first mask session, tear film parameters (NIBUT and LLT) improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the past years showed that various factors can cause corneal injuries, including the inflammatory causes of neovascularization; for example, ocular mucous membrane pemphigoid (MMP) can induce an inflammatory response that leads to the formation of a fibrotic scar [ 14 ], Sjögren's syndrome can cause keratitis sicca with inflammation [ 15 ]. Moreover, ocular graft-versus-host disease affects all the structures of the entire ocular surface system, including lacrimal and meibomian glands, cornea, conjunctiva, eyelids, nasolacrimal duct, and tears [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 The slit lamp examination reveals redness, conjunctival keratinization with chalasis, and punctate or filamentous keratitis. [41][42][43][44][45][46] Other ocular manifestations of pSS which have been reported include episcleritis/scleritis, uveitis, retinal vasculitis, cicatrizing conjunctivitis, sterile corneal ulcer/infiltration, corneal melting perforation and optic neuritis. 47…”
Section: Ocular Involvement In Pssmentioning
confidence: 99%